2012
DOI: 10.1111/j.1742-481x.2012.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Wound infection, dressings and pain, is there a relationship in the chronic wound?

Abstract: The focus on quality of life issues in wound care has justly taken a far greater importance. With the acceptance that pain can be a major factor to the patient, and in particular, pain at dressing change comes the opportunity for avoidance and/or reduction strategies. Whilst pain has been associated with wound infection for millennia, it is only much more recently that this has received due attention from research and clinical practice. In this study, the nature of pain, changes in pain and pain associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
1
19
1
1
Order By: Relevance
“…There was one systematic review—level I evidence which compared the value in identifying pathogens between wound swab and wound biopsy techniques. Six expert opinion or consensus documents, which focused on diagnosis of infection in chronic wounds and/or CLUs were also included . Of the remaining 73 articles, eleven focused on clinical signs and symptoms of infection in chronic wounds, 12 focused on diagnosis of infection, and 50 examined the effectiveness of numerous treatment methods for chronic wound infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was one systematic review—level I evidence which compared the value in identifying pathogens between wound swab and wound biopsy techniques. Six expert opinion or consensus documents, which focused on diagnosis of infection in chronic wounds and/or CLUs were also included . Of the remaining 73 articles, eleven focused on clinical signs and symptoms of infection in chronic wounds, 12 focused on diagnosis of infection, and 50 examined the effectiveness of numerous treatment methods for chronic wound infection.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (two cross‐sectional studies, one Delphi study and one case study) concluded increasing pain was diagnostic of chronic wound infection. It is essential to differentiate between pain related to infection and pain related to venous hypertension or other causes.…”
Section: Resultsmentioning
confidence: 99%
“…We identified the most frequent eight outcome domains that were included in 25% or more of the included protocols, leaving the majority of outcome domains ( n = 118) being used relatively infrequently. While complete wound healing has been recommended as the most important clinically relevant outcome in many cases, there frequently is focus on the surrogate or interim outcome of changes in wound size . Other important outcomes include wound infection, which can be captured in several different ways, such as pain and quality of life …”
Section: Discussionmentioning
confidence: 99%
“…This finding echoed that of Saldanha et al, where primary outcomes were the most well specified. However, there are objective definitions of healing available; for example, a large RCT of a leg ulcer intervention defined healing of venous leg ulcer as “complete epithelial cover in the absence of a scab (eschar) with no dressing required.” The Food and Drug Administration (FDA) defines complete wound closure as “skin reepithelialisation without drainage or dressing requirements, confirmed at two consecutive study visits two weeks apart, and the time should be specified when being analyzed.” None of the review protocols we examined used these or similar definitions of wound healing. Secondary outcomes such as pain, quality of life, and cost were generally the least‐well specified elements.…”
Section: Discussionmentioning
confidence: 99%
“…13 As well as impairing wound healing, clinical infection may increase the severity of wound-related pain 14,15 and have a direct effect on patient comfort. Indeed, Cutting et al 16 reported on a multinational, multidisciplinary Delphi study that revealed a causal relationship between wound infection and the onset or change in the nature of pain: 15/21 respondents identified this as an issue in event-related pain and 19/21 cited this phenomenon in somatic-related pain, with 17/21 respondents citing that patients with wound infection generally experienced more pain than those who were free of infection. In addition, 20/21 clinicians thought that some types of dressing caused pain during dressing change.…”
Section: Antimicrobial Therapymentioning
confidence: 99%